Prevalence of traded bird species in key biodiversity areas - Oscar Morton; Tom Lansley; Stuart H. M. Butchart; Graeme M. Buchanan; David P. Edwards (Conservation Biology, 2026)
The use and trade of biodiversity involve tens of thousands of species that are exploited at a range of scales, intensities, and degrees of sustainability. As a result, some are highly threatened. Key biodiversity areas (KBAs) are sites of significance for the persistence of biodiversity identified nationally based on standardized criteria. The degree to which biodiversity in KBAs is likely to be used and traded is not well understood. We undertook a fine‐scale assessment of the area of habitat (AOH) of traded species in KBAs. We used data on >16,000 KBAs and combined these with AOH maps for >10,000 bird species, a heavily traded and well‐documented indicator taxon. We subsequently mapped and quantified the distribution of traded species richness, extinction risk, and range‐size rarity in and adjacent to KBAs. Although less than half of all bird species are traded, we found that most bird species in KBAs were traded, and the richness of traded species was more than twice (119%) that of nontraded species. Traded species had comparable proportions of their AOH (22.5% on average) in KBAs as nontraded species (21.5%). Global hotspots of richness, extinction risk, and range rarity for traded species disproportionately occurred in KBAs, which had higher levels of extinction risk and range rarity for traded species than locations immediately outside KBAs. Of the 46 species that are likely threatened by unsustainable use and have the majority of their habitat falling within KBAs, we found that eight species had no habitat in designated protected areas. Reconciling sustainable use and the critical importance of KBAs for threatened species is essential. Our results suggest that for some species, there is an urgent need to protect key sites and ensure that any use and trade of species within them are sustainable.

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Mapping area of habitat for inland wetland species - Francesca A. Ridley; Catherine A. Sayer; Louise Mair; Daniele Baisero; Monika Böhm; Thomas M. Brooks; Stuart H. M. Butchart; Viola Clausnitzer; Jeorg Freyhof; Günther Grill; Ian Harrison; Randall R. Jiménez; et al. (Conservation Biology, 2026)
Area of habitat (AOH) maps provide a high‐resolution representation of the habitat available in a species’ range and can support conservation policy and planning processes. However, until recently, there was insufficient knowledge on the distribution of inland wetlands and freshwater biodiversity to develop AOH mapping methods specifically tailored to inland wetlands. We used a combined empirical and thematic approach to translate inland wetland habitat classes in the International Union for Conservation of Nature (IUCN) Habitats Classification Scheme into spatially explicit wetland‐cover types derived from the Global Lakes and Wetlands Database 2 and the World Karst Aquifer Map. The AOH was subsequently estimated as the area in the mapped range that corresponded to each species’ habitat and elevation associations. We developed and tested the method with IUCN Red List assessment data, range maps, and point locality data for fishes, odonates, decapod crustaceans, and mollusks (22,876 species). The method performed well in comparison with similar methods already developed for terrestrial mammals, birds, amphibians, and reptiles. The mean map prevalence (proportion of area in a species’ range that was AOH) was 18–32% for each taxonomic group. Based on data on known localities of occurrence, 78–100% of species per taxonomic group had a higher classification accuracy than expected if AOH were distributed in the range at random. This represents an increased accuracy in the distribution of wetland species. Our study represents the first attempt to distinguish between inland wetland habitat subclasses and to include subterranean habitats in an AOH mapping method. Our method will facilitate the inclusion of previously underrepresented taxa in key conservation tools and analyses and is expected to increase the accuracy of AOH mapping for any species associated with inland wetlands.

Effectiveness of Key Biodiversity Areas in representing global avian diversity - Tom P. Lansley; Olivia Crowe; Stuart H. M. Butchart; David P. Edwards; Gavin H. Thomas (Conservation Biology, 2025)
Key Biodiversity Areas (KBAs) are the largest and most complete network of significant sites for the global persistence of biodiversity. Although important sites for birds worldwide have been relatively well assessed, a key question is how effectively the global KBA network represents avian diversity. We identified bird species, orders, habitats, and geographic regions that are underrepresented by KBAs. Area of Habitat (AOH) maps for 10,517 terrestrial bird species were cropped and masked by the extent of each KBA. Almost all species had at least one part of their seasonal distribution in one or more KBAs. Twenty‐nine species had no habitat overlap with KBAs, and 1900 species had 2 ). Terrestrial bird species of tropical forests were 12.8% better represented in KBAs than expected by chance, whereas boreal and temperate forest species were less well represented than expected by chance (74.4% and 25.1%, respectively). Among avian orders, Anseriformes and Charadriiformes were underrepresented in KBAs (29.0% and 17.9%, respectively), whereas Trogoniformes and Psittaciformes were better represented (16.2% and 6.9%, respectively) than expected by chance. Bird species for potential KBA identification include marsh antwren ( Formicivora paludicola ) and Tabar pitta ( Erythropitta splendida ). These are mainly due to recent changes in species’ taxonomy or their International Union for Conservation of Nature Red List category. Identifying poorly represented species and where they occur highlights shortfalls where expansion of the network could bring conservation benefits.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Accelerating and standardising IUCN Red List assessments with sRedList - Victor Cazalis; Moreno Di Marco; Alexander Zizka; Stuart H.M. Butchart; Manuela González-Suárez; Monika Böhm; Steven P. Bachman; Michael Hoffmann; Ilaria Rosati; Francesco De Leo; Martin Jung; Ana Benítez-López; et al. (Biological Conservation, 2024)

Assessing the global prevalence of wild birds in trade - Paul F. Donald; Eresha Fernando; Lauren Brown; Michela Busana; Stuart H. M. Butchart; Serene Chng; Alicia de la Colina; Juliana Machado Ferreira; Anuj Jain; Victoria R. Jones; Rocio Lapido; Kelly Malsch; et al. (Conservation Biology, 2024)
Trade represents a significant threat to many wild species and is often clandestine and poorly monitored. Information on which species are most prevalent in trade and potentially threatened by it therefore remains fragmentary. We used 7 global data sets on birds in trade to identify species or groups of species at particular risk and assessed the extent to which they were congruent in terms of the species recorded in trade. We used the frequency with which species were recorded in the data sets as the basis for a trade prevalence score that was applied to all bird species globally. Literature searches and questionnaire surveys were used to develop a list of species known to be heavily traded to validate the trade prevalence score. The score was modeled to identify significant predictors of trade. Although the data sets sampled different parts of the broad trade spectrum, congruence among them was statistically strong in all comparisons. Furthermore, the frequency with which species were recorded within data sets was positively correlated with their occurrence across data sets, indicating that the trade prevalence score captured information on trade volume. The trade prevalence score discriminated well between species identified from semi‐independent assessments as heavily or unsustainably traded and all other species. Globally, 45.1% of all bird species and 36.7% of globally threatened bird species had trade prevalence scores ≥1. Species listed in Appendices I or II of CITES, species with large geographical distributions, and nonpasserines tended to have high trade prevalence scores. Speciose orders with high mean trade prevalence scores included Falconiformes, Psittaciformes, Accipitriformes, Anseriformes, Bucerotiformes, and Strigiformes. Despite their low mean prevalence score, Passeriformes accounted for the highest overall number of traded species of any order but had low representation in CITES appendices. Geographical hotspots where large numbers of traded species co‐occur differed among passerines (Southeast Asia and Eurasia) and nonpasserines (central South America, sub‐Saharan Africa, and India). This first attempt to quantify and map the relative prevalence in trade of all bird species globally can be used to identify species and groups of species that may be at particular risk of harm from trade and can inform conservation and policy interventions to reduce its adverse impacts.

Rates of tree cover loss in key biodiversity areas on Indigenous Peoples’ lands - Ashley Thomas Simkins; Paul F. Donald; Alison E. Beresford; Stuart H. M. Butchart; Julia E. Fa; Alvaro Onrubia Fernández‐Llamazares; Stephen T. Garnett; Graeme M. Buchanan (Conservation Biology, 2024)
Indigenous Peoples’ lands (IPL) cover at least 38 million km 2 (28.1%) of Earth's terrestrial surface. These lands can be important for biodiversity conservation. Around 20.7% of IPL intersect areas protected by government (PAs). Many sites of importance for biodiversity within IPL could make a substantial but hitherto unquantified contribution to global site‐based conservation targets. Key Biodiversity Areas (KBAs) represent the largest global network of systematically identified sites of high importance for biodiversity. We assessed the effectiveness of IPL in slowing biodiversity loss inside and outside PAs by quantifying tree cover loss from 2000 to 2019 in KBAs at international and national levels and comparing it with losses at equivalent sites outside mapped IPL. Based on a matched sample of 1‐km 2 cells in KBAs inside and outside mapped IPL, tree cover loss in KBAs outside PAs was lower inside IPL than outside IPL. By contrast, tree cover loss in KBAs inside PAs was lower outside IPL than inside IPL (although the difference was far smaller). National rates of tree cover loss in KBAs varied greatly in relation to their IPL and PA status. In one half of the 44 countries we examined individually, there was no significant difference in the rate of tree cover loss in KBAs inside and outside mapped IPL. The reasons for this intercountry variation could illuminate the importance of IPL in meeting the Convention on Biological Diversity's ambition of conserving 30% of land by 2030. Critical to this will be coordinated action by governments to strengthen and enforce Indigenous Peoples’ rights, secure their collective systems of tenure and governance, and recognize their aspirations for their lands and futures.

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Modelling the probability of meeting IUCN Red List criteria to support reassessments - Etienne G. Henry; Luca Santini; Stuart H. M. Butchart; Manuela González‐Suárez; Pablo M. Lucas; Ana Benítez‐López; Giordano Mancini; Martin Jung; Pedro Cardoso; Alexander Zizka; Carsten Meyer; H. Reşit Akçakaya; et al. (Global Change Biology, 2024)
Comparative extinction risk analysis—which predicts species extinction risk from correlation with traits or geographical characteristics—has gained research attention as a promising tool to support extinction risk assessment in the IUCN Red List of Threatened Species. However, its uptake has been very limited so far, possibly because existing models only predict a species' Red List category, without indicating which Red List criteria may be triggered. This prevents such approaches to be integrated into Red List assessments. We overcome this implementation gap by developing models that predict the probability of species meeting individual Red List criteria. Using data on the world's birds, we evaluated the predictive performance of our criterion‐specific models and compared it with the typical criterion‐blind modelling approach. We compiled data on biological traits (e.g. range size, clutch size) and external drivers (e.g. change in canopy cover) often associated with extinction risk. For each specific criterion, we modelled the relationship between extinction risk predictors and species' Red List category under that criterion using ordinal regression models. We found criterion‐specific models were better at identifying threatened species compared to a criterion‐blind model (higher sensitivity), but less good at identifying not threatened species (lower specificity). As expected, different covariates were important for predicting extinction risk under different criteria. Change in annual temperature was important for criteria related to population trends, while high forest dependency was important for criteria related to restricted area of occupancy or small population size. Our criteria‐specific method can support Red List assessors by producing outputs that identify species likely to meet specific criteria, and which are the most important predictors. These species can then be prioritised for re‐evaluation. We expect this new approach to increase the uptake of extinction risk models in Red List assessments, bridging a long‐standing research‐implementation gap.

Prioritizing the reassessment of data‐deficient species on the IUCN Red List - Victor Cazalis; Luca Santini; Pablo M. Lucas; Manuela González‐Suárez; Michael Hoffmann; Ana Benítez‐López; Michela Pacifici; Aafke M. Schipper; Monika Böhm; Alexander Zizka; Viola Clausnitzer; Carsten Meyer; et al. (Conservation Biology, 2023)
Despite being central to the implementation of conservation policies, the usefulness of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species is hampered by the 14% of species classified as data‐deficient (DD) because information to evaluate these species’ extinction risk was lacking when they were last assessed or because assessors did not appropriately account for uncertainty. Robust methods are needed to identify which DD species are more likely to be reclassified in one of the data‐sufficient IUCN Red List categories. We devised a reproducible method to help red‐list assessors prioritize reassessment of DD species and tested it with 6887 DD species of mammals, reptiles, amphibians, fishes, and Odonata (dragonflies and damselflies). For each DD species in these groups, we calculated its probability of being classified in a data‐sufficient category if reassessed today from covariates measuring available knowledge (e.g., number of occurrence records or published articles available), knowledge proxies (e.g., remoteness of the range), and species characteristics (e.g., nocturnality); calculated change in such probability since last assessment from the increase in available knowledge (e.g., new occurrence records); and determined whether the species might qualify as threatened based on recent rate of habitat loss determined from global land‐cover maps. We identified 1907 species with a probability of being reassessed in a data‐sufficient category of >0.5; 624 species for which this probability increased by >0.25 since last assessment; and 77 species that could be reassessed as near threatened or threatened based on habitat loss. Combining these 3 elements, our results provided a list of species likely to be data‐sufficient such that the comprehensiveness and representativeness of the IUCN Red List can be improved.

Introducing a common taxonomy to support learning from failure in conservation - Iain Dickson; Stuart H. M. Butchart; Allison Catalano; David Gibbons; Julia P. G. Jones; Katie Lee‐Brooks; Thomasina Oldfield; David Noble; Stuart Paterson; Sugoto Roy; Julien Semelin; Paul Tinsley‐Marshall; et al. (Conservation Biology, 2023)
Although some sectors have made significant progress in learning from failure, there is currently limited consensus on how a similar transition could best be achieved in conservation and what is required to facilitate this. One of the key enabling conditions for other sectors is a widely accepted and standardized classification system for identifying and analyzing root causes of failure. We devised a comprehensive taxonomy of root causes of failure affecting conservation projects. To develop this, we solicited examples of real‐life conservation efforts that were deemed to have failed in some way, identified their underlying root causes of failure, and used these to develop a generic, 3‐tier taxonomy of the ways in which projects fail, at the top of which are 6 overarching cause categories that are further divided into midlevel cause categories and specific root causes. We tested the taxonomy by asking conservation practitioners to use it to classify the causes of failure for conservation efforts they had been involved in. No significant gaps or redundancies were identified during this testing phase. We then analyzed the frequency that particular root causes were encountered by projects within this test sample, which suggested that some root causes were more likely to be encountered than others and that a small number of root causes were more likely to be encountered by projects implementing particular types of conservation action. Our taxonomy could be used to improve identification, analysis, and subsequent learning from failed conservation efforts, address some of the barriers that currently limit the ability of conservation practitioners to learn from failure, and contribute to establishing an effective culture of learning from failure within conservation.

Connectivity between countries established by landbirds and raptors migrating along the African–Eurasian flyway - João L. Guilherme; Victoria R. Jones; Inês Catry; Martin Beal; Maria P. Dias; Steffen Oppel; Juliet A. Vickery; Chris M. Hewson; Stuart H. M. Butchart; Ana S. L. Rodrigues (Conservation Biology, 2023)
The conservation of long‐distance migratory birds requires coordination between the multiple countries connected by the movements of these species. The recent expansion of tracking studies is shedding new light on these movements, but much of this information is fragmented and inaccessible to conservation practitioners and policy makers. We synthesized current knowledge on the connectivity established between countries by landbirds and raptors migrating along the African–Eurasian flyway. We reviewed tracking studies to compile migration records for 1229 individual birds, from which we derived 544 migratory links, each link corresponding to a species’ connection between a breeding country in Europe and a nonbreeding country in sub‐Saharan Africa. We used these migratory links to analyze trends in knowledge over time and spatial patterns of connectivity per country (across species), per species (across countries), and at the flyway scale (across all countries and all species). The number of tracking studies available increased steadily since 2010 (particularly for landbirds), but the coverage of existing tracking data was highly incomplete. An average of 7.5% of migratory landbird species and 14.6% of raptor species were tracked per country. More data existed from central and western European countries, and it was biased toward larger bodied species. We provide species‐ and country‐level syntheses of the migratory links we identified from the reviewed studies, involving 123 populations of 43 species, migrating between 28 European and 43 African countries. Several countries (e.g., Spain, Poland, Ethiopia, Democratic Republic of Congo) are strategic priorities for future tracking studies to complement existing data, particularly on landbirds. Despite the limitations in existing tracking data, our data and results can inform discussions under 2 key policy instruments at the flyway scale: the African–Eurasian Migratory Landbirds Action Plan and the Memorandum of Understanding on the Conservation of Migratory Birds of Prey in Africa and Eurasia.

Funding evidence‐based conservation - Danni Parks; Nida Al‐Fulaij; Clare Brook; Stuart H. M. Butchart; Jean‐Gaël Collomb; David Cope; Simon Dowell; Becky Falkingham; Winifred F. Frick; Douglas Gibbs; Emily E. Gray; Nicolas Heard; et al. (Conservation Biology, 2022)

Translating habitat class to land cover to map area of habitat of terrestrial vertebrates - Maria Lumbierres; Prabhat Raj Dahal; Moreno Di Marco; Stuart H. M. Butchart; Paul F. Donald; Carlo Rondinini (Conservation Biology, 2022)
Area of habitat (AOH) is defined as the “habitat available to a species, that is, habitat within its range” and is calculated by subtracting areas of unsuitable land cover and elevation from the range. The International Union for the Conservation of Nature (IUCN) Habitats Classification Scheme provides information on species habitat associations, and typically unvalidated expert opinion is used to match habitat to land‐cover classes, which generates a source of uncertainty in AOH maps. We developed a data‐driven method to translate IUCN habitat classes to land cover based on point locality data for 6986 species of terrestrial mammals, birds, amphibians, and reptiles. We extracted the land‐cover class at each point locality and matched it to the IUCN habitat class or classes assigned to each species occurring there. Then, we modeled each land‐cover class as a function of IUCN habitat with (SSG, using) logistic regression models. The resulting odds ratios were used to assess the strength of the association between each habitat and land‐cover class. We then compared the performance of our data‐driven model with those from a published translation table based on expert knowledge. We calculated the association between habitat classes and land‐cover classes as a continuous variable, but to map AOH as binary presence or absence, it was necessary to apply a threshold of association. This threshold can be chosen by the user according to the required balance between omission and commission errors. Some habitats (e.g., forest and desert) were assigned to land‐cover classes with more confidence than others (e.g., wetlands and artificial). The data‐driven translation model and expert knowledge performed equally well, but the model provided greater standardization, objectivity, and repeatability. Furthermore, our approach allowed greater flexibility in the use of the results and uncertainty to be quantified. Our model can be modified for regional examinations and different taxonomic groups.

Setting priorities for climate change adaptation of Critical Sites in the Africa‐Eurasian waterbird flyways - Frank T. Breiner; Mira Anand; Stuart H. M. Butchart; Martina Flörke; Etienne Fluet‐Chouinard; Antoine Guisan; Lammert Hilarides; Victoria R. Jones; Mikhail Kalyakin; Bernhard Lehner; Merijn van Leeuwen; James W. Pearce‐Higgins; et al. (Global Change Biology, 2022)
Despite their importance for biodiversity and ecosystem services, wetlands are among the most threatened ecosystems globally. The conservation of many migratory waterbirds depends on the conservation of a network of key sites along their flyways. However, the suitability of these sites is changing under climate change, and it is important that management of individual sites in the network adapts to these changes. Using bioclimatic models that also account for changes in inundation, we found that projected climate change will reduce habitat suitability for waterbirds at 57.5% of existing Critical Sites within Africa‐Eurasia, varying from 20.1% in Eastern Europe to 87.0% in Africa. African and Middle East sites are particularly threatened, comprising 71 of the 100 most vulnerable sites. By highlighting priority sites for conservation and classifying Critical Sites into Climate Change Adaptation Strategy (CCAS) classes, our results can be used to support the climate change adaptation of both individual sites and the entire site network.

A quantitative global review of species population monitoring - Caroline Moussy; Ian J. Burfield; P. J. Stephenson; Arabella F. E. Newton; Stuart H. M. Butchart; William J. Sutherland; Richard D. Gregory; Louise McRae; Philip Bubb; Ignacio Roesler; Cynthia Ursino; Yanqing Wu; et al. (Conservation Biology, 2022)
Species monitoring, defined here as the repeated, systematic collection of data to detect long‐term changes in the populations of wild species, is a vital component of conservation practice and policy. We created a database of nearly 1200 schemes, ranging in start date from 1800 to 2018, to review spatial, temporal, taxonomic, and methodological patterns in global species monitoring. We identified monitoring schemes through standardized web searches, an online survey of stakeholders, in‐depth national searches in a sample of countries, and a review of global biodiversity databases. We estimated the total global number of monitoring schemes operating at 3300–15,000. Since 2000, there has been a sharp increase in the number of new schemes being initiated in lower‐ and middle‐income countries and in megadiverse countries, but a decrease in high‐income countries. The total number of monitoring schemes in a country and its per capita gross domestic product were strongly, positively correlated. Schemes that were active in 2018 had been running for an average of 21 years in high‐income countries, compared with 13 years in middle‐income countries and 10 years in low‐income countries. In high‐income countries, over one‐half of monitoring schemes received government funding, but this was less than one‐quarter in low‐income countries. Data collection was undertaken partly or wholly by volunteers in 37% of schemes, and such schemes covered significantly more sites and species than those undertaken by professionals alone. Birds were by far the most widely monitored taxonomic group, accounting for around half of all schemes, but this bias declined over time. Monitoring in most taxonomic groups remains sparse and uncoordinated, and most of the data generated are elusive and unlikely to feed into wider biodiversity conservation processes. These shortcomings could be addressed by, for example, creating an open global meta‐database of biodiversity monitoring schemes and enhancing capacity for species monitoring in countries with high biodiversity. Article impact statement : Species population monitoring for conservation purposes remains strongly biased toward a few vertebrate taxa in wealthier countries.

Generation lengths of the world's birds and their implications for extinction risk - Jeremy P. Bird; Robert Martin; H. Reşit Akçakaya; James Gilroy; Ian J. Burfield; Stephen T. Garnett; Andy Symes; Joseph Taylor; Çağan H. Şekercioğlu; Stuart H. M. Butchart (Conservation Biology, 2020)
Birds have been comprehensively assessed on the International Union for Conservation of Nature (IUCN) Red List more times than any other taxonomic group. However, to date, generation lengths have not been systematically estimated to scale population trends when undertaking assessments, as required by the criteria of the IUCN Red List. We compiled information from major databases of published life‐history and trait data for all birds and imputed missing life‐history data as a function of species traits with generalized linear mixed models. Generation lengths were derived for all species, based on our modeled values of age at first breeding, maximum longevity, and annual adult survival. The resulting generation lengths varied from 1.42 to 27.87 years (median 2.99). Most species (61%) had generation lengths

Relating characteristics of global biodiversity targets to reported progress - Elizabeth J. Green; Graeme M. Buchanan; Stuart H. M. Butchart; Georgina M. Chandler; Neil D. Burgess; Samantha L. L. Hill; Richard D. Gregory (Conservation Biology, 2019)
To inform governmental discussions on the nature of a revised Strategic Plan for Biodiversity of the Convention on Biological Diversity (CBD), we reviewed the relevant literature and assessed the framing of the 20 Aichi Biodiversity Targets in the current strategic plan. We asked international experts from nongovernmental organizations, academia, government agencies, international organizations, research institutes, and the CBD to score the Aichi Targets and their constituent elements against a set of specific, measurable, ambitious, realistic, unambiguous, scalable, and comprehensive criteria (SMART based, excluding time bound because all targets are bound to 2015 or 2020). We then investigated the relationship between these expert scores and reported progress toward the target elements by using the findings from 2 global progress assessments (Global Biodiversity Outlook and the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services). We analyzed the data with ordinal logistic regressions. We found significant positive relationships ( p

Applying habitat and population‐density models to land‐cover time series to inform IUCN Red List assessments - Luca Santini; Stuart H. M. Butchart; Carlo Rondinini; Ana Benítez‐López; Jelle P. Hilbers; Aafke M. Schipper; Mirza Cengic; Joseph A. Tobias; Mark A. J. Huijbregts (Conservation Biology, 2019)
The IUCN (International Union for Conservation of Nature) Red List categories and criteria are the most widely used framework for assessing the relative extinction risk of species. The criteria are based on quantitative thresholds relating to the size, trends, and structure of species’ distributions and populations. However, data on these parameters are sparse and uncertain for many species and unavailable for others, potentially leading to their misclassification or classification as data deficient. We devised an approach that combines data on land‐cover change, species‐specific habitat preferences, population abundance, and dispersal distance to estimate key parameters (extent of occurrence, maximum area of occupancy, population size and trend, and degree of fragmentation) and hence predict IUCN Red List categories for species. We applied our approach to nonpelagic birds and terrestrial mammals globally (∼15,000 species). The predicted categories were fairly consistent with published IUCN Red List assessments, but more optimistic overall. We predicted 4.2% of species (467 birds and 143 mammals) to be more threatened than currently assessed and 20.2% of data deficient species (10 birds and 114 mammals) to be at risk of extinction. Incorporating the habitat fragmentation subcriterion reduced these predictions 1.5–2.3% and 6.4–14.9% (depending on the quantitative definition of fragmentation) for threatened and data deficient species, respectively, highlighting the need for improved guidance for IUCN Red List assessors on the application of this aspect of the IUCN Red List criteria. Our approach complements traditional methods of estimating parameters for IUCN Red List assessments. Furthermore, it readily provides an early‐warning system to identify species potentially warranting changes in their extinction‐risk category based on periodic updates of land‐cover information. Given our method relies on optimistic assumptions about species distribution and abundance, all species predicted to be more at risk than currently evaluated should be prioritized for reassessment.

Rapid ecosystem service assessment of the impact of Koshi Tappu Wildlife Reserve on wetland benefits to local communities - Jennifer C. Merriman; Hum Gurung; Shalu Adhikari; Stuart H. M. Butchart; Top B. Khatri; Ravi S. Pandit; Ashok K. Ram; David H. L. Thomas; Ishana Thapa (Wetlands Ecology and Management, 2018)

Clarifying the key biodiversity areas partnership and programme - Simon N. Stuart; Thomas M. Brooks; Stuart H. M. Butchart; Wendy Elliott; Melanie Heath; Dieter Hoffmann; Leslie Honey; Irina Kostadinova; Penny Langhammer; Olivier Langrand; Susan Lieberman; Daniel Marnewick; et al. (Biodiversity and Conservation, 2018)

Population density–range size relationship revisited - Maria Novosolov; Gordon H. Rodda; Alexandra C. North; Stuart H. M. Butchart; Oliver J. S. Tallowin; Alison M. Gainsbury; Shai Meiri (Global Ecology and Biogeography, 2017)
Aim The species population density–range size relationship posits that locally abundant species are widely distributed. However, this proposed pattern has been insufficiently tested. The few tests conducted were usually limited in scale and gave conflicting results. We tested the generality of the positive population density–range size relationship. We then studied whether similar environmental niche requirements are correlated with range size and with population density to search for mechanisms driving the hypothesized link between population density and range size. Location Worldwide. Methods We collected data on population density, range size and environmental niche for a global dataset of 192 lizard, 893 bird and 350 mammal species. Assessing the relationship between population density and range size and environmental niche parameters, we corrected for phylogenetic relationships, body mass, diet and study area. Results Our findings reveal that density had a weak negative correlation with bird range size and was unrelated to lizard and mammal range size. These trends were consistent at the global scale and across the biogeographical realms. Range size was related to relatively similar environmental niche parameters in all groups. Population density, however, was explained by taxon‐specific factors and was therefore unrelated to range size by common causation. Main conclusions We suggest that the positive relationship between population density and range size identified in previous studies might be an artefact arising through incomplete sampling of range sizes. Our results indicate that the mechanisms shaping population density and range size may be independent.

Choice of baseline climate data impacts projected species' responses to climate change - David J. Baker; Andrew J. Hartley; Stuart H. M. Butchart; Stephen G. Willis (Global Change Biology, 2016)
Climate data created from historic climate observations are integral to most assessments of potential climate change impacts, and frequently comprise the baseline period used to infer species‐climate relationships. They are often also central to downscaling coarse resolution climate simulations from General Circulation Models ( GCM s) to project future climate scenarios at ecologically relevant spatial scales. Uncertainty in these baseline data can be large, particularly where weather observations are sparse and climate dynamics are complex (e.g. over mountainous or coastal regions). Yet, importantly, this uncertainty is almost universally overlooked when assessing potential responses of species to climate change. Here, we assessed the importance of historic baseline climate uncertainty for projections of species' responses to future climate change. We built species distribution models ( SDM s) for 895 African bird species of conservation concern, using six different climate baselines. We projected these models to two future periods (2040–2069, 2070–2099), using downscaled climate projections, and calculated species turnover and changes in species‐specific climate suitability. We found that the choice of baseline climate data constituted an important source of uncertainty in projections of both species turnover and species‐specific climate suitability, often comparable with, or more important than, uncertainty arising from the choice of GCM . Importantly, the relative contribution of these factors to projection uncertainty varied spatially. Moreover, when projecting SDM s to sites of biodiversity importance (Important Bird and Biodiversity Areas), these uncertainties altered site‐level impacts, which could affect conservation prioritization. Our results highlight that projections of species' responses to climate change are sensitive to uncertainty in the baseline climatology. We recommend that this should be considered routinely in such analyses.

Impact of alternative metrics on estimates of extent of occurrence for extinction risk assessment - Lucas N. Joppa; Stuart H. M. Butchart; Michael Hoffmann; Steve P. Bachman; H. Resit Akçakaya; Justin F. Moat; Monika Böhm; Robert A. Holland; Adrian Newton; Beth Polidoro; Adrian Hughes (Conservation Biology, 2016)
In International Union for Conservation of Nature (IUCN) Red List assessments, extent of occurrence (EOO) is a key measure of extinction risk. However, the way assessors estimate EOO from maps of species’ distributions is inconsistent among assessments of different species and among major taxonomic groups. Assessors often estimate EOO from the area of mapped distribution, but these maps often exclude areas that are not habitat in idiosyncratic ways and are not created at the same spatial resolutions. We assessed the impact on extinction risk categories of applying different methods (minimum convex polygon, alpha hull) for estimating EOO for 21,763 species of mammals, birds, and amphibians. Overall, the percentage of threatened species requiring down listing to a lower category of threat (taking into account other Red List criteria under which they qualified) spanned 11–13% for all species combined (14–15% for mammals, 7–8% for birds, and 12–15% for amphibians). These down listings resulted from larger estimates of EOO and depended on the EOO calculation method. Using birds as an example, we found that 14% of threatened and near threatened species could require down listing based on the minimum convex polygon (MCP) approach, an approach that is now recommended by IUCN. Other metrics (such as alpha hull) had marginally smaller impacts. Our results suggest that uniformly applying the MCP approach may lead to a one‐time down listing of hundreds of species but ultimately ensure consistency across assessments and realign the calculation of EOO with the theoretical basis on which the metric was founded.

Migratory diversity predicts population declines in birds - James J. Gilroy; Jennifer A. Gill; Stuart H. M. Butchart; Victoria R. Jones; Aldina M. A. Franco (Ecology Letters, 2016)
Declines in migratory species are a pressing concern worldwide, but the mechanisms underpinning these declines are not fully understood. We hypothesised that species with greater within‐population variability in migratory movements and destinations, here termed ‘migratory diversity’, might be more resilient to environmental change. To test this, we related map‐based metrics of migratory diversity to recent population trends for 340 European breeding birds. Species that occupy larger non‐breeding ranges relative to breeding, a characteristic we term ‘migratory dispersion’, were less likely to be declining than those with more restricted non‐breeding ranges. Species with partial migration strategies (i.e. overlapping breeding and non‐breeding ranges) were also less likely to be declining than full migrants or full residents, an effect that was independent of migration distance. Recent rates of advancement in Europe‐wide spring arrival date were greater for partial migrants than full migrants, suggesting that migratory diversity may also help facilitate species responses to climate change.

Ecological and socio-economic factors affecting extinction risk in parrots - George Olah; Stuart H. M. Butchart; Andy Symes; Iliana Medina Guzmán; Ross Cunningham; Donald J. Brightsmith; Robert Heinsohn (Biodiversity and Conservation, 2016)

Synergies and trade‐offs in achieving global biodiversity targets - Moreno Di Marco; Stuart H. M. Butchart; Piero Visconti; Graeme M. Buchanan; Gentile F. Ficetola; Carlo Rondinini (Conservation Biology, 2016)
After their failure to achieve a significant reduction in the global rate of biodiversity loss by 2010, world governments adopted 20 new ambitious Aichi biodiversity targets to be met by 2020. Efforts to achieve one particular target can contribute to achieving others, but different targets may sometimes require conflicting solutions. Consequently, lack of strategic thinking might result, once again, in a failure to achieve global commitments to biodiversity conservation. We illustrate this dilemma by focusing on Aichi Target 11. This target requires an expansion of terrestrial protected area coverage, which could also contribute to reducing the loss of natural habitats (Target 5), reducing human‐induced species decline and extinction (Target 12), and maintaining global carbon stocks (Target 15). We considered the potential impact of expanding protected areas to mitigate global deforestation and the consequences for the distribution of suitable habitat for >10,000 species of forest vertebrates (amphibians, birds, and mammals). We first identified places where deforestation might have the highest impact on remaining forests and then identified places where deforestation might have the highest impact on forest vertebrates (considering aggregate suitable habitat for species). Expanding protected areas toward locations with the highest deforestation rates (Target 5) or the highest potential loss of aggregate species’ suitable habitat (Target 12) resulted in partially different protected area network configurations (overlapping with each other by about 73%). Moreover, the latter approach contributed to safeguarding about 30% more global carbon stocks than the former. Further investigation of synergies and trade‐offs between targets would shed light on these and other complex interactions, such as the interaction between reducing overexploitation of natural resources (Targets 6, 7), controlling invasive alien species (Target 9), and preventing extinctions of native species (Target 12). Synergies between targets must be identified and secured soon and trade‐offs must be minimized before the options for co‐benefits are reduced by human pressures.

Prioritizing islands for the eradication of invasive vertebrates in the United Kingdom overseas territories - Jeffrey Dawson; Steffen Oppel; Richard J. Cuthbert; Nick Holmes; Jeremy P. Bird; Stuart H. M. Butchart; Dena R. Spatz; Bernie Tershy (Conservation Biology, 2015)
Invasive alien species are one of the primary threats to native biodiversity on islands worldwide. Consequently, eradicating invasive species from islands has become a mainstream conservation practice. Deciding which islands have the highest priority for eradication is of strategic importance to allocate limited resources to achieve maximum conservation benefit. Previous island prioritizations focused either on a narrow set of native species or on a small geographic area. We devised a prioritization approach that incorporates all threatened native terrestrial vertebrates and all invasive terrestrial vertebrates occurring on 11 U.K. overseas territories, which comprise over 2000 islands ranging from the sub‐Antarctic to the tropics. Our approach includes eradication feasibility and distinguishes between the potential and realistic conservation value of an eradication, which reflects the benefit that would accrue following eradication of either all invasive species or only those species for which eradication techniques currently exist. We identified the top 25 priority islands for invasive species eradication that together would benefit extant populations of 155 native species including 45 globally threatened species. The 5 most valuable islands included the 2 World Heritage islands Gough (South Atlantic) and Henderson (South Pacific) that feature unique seabird colonies, and Anegada, Little Cayman, and Guana Island in the Caribbean that feature a unique reptile fauna. This prioritization can be rapidly repeated if new information or techniques become available, and the approach could be replicated elsewhere in the world. Priorización de Islas para la Erradicación de Vertebrados Invasores en los Territorios Exteriores del Reino Unido

Potential impact of invasive alien species on ecosystem services provided by a tropical forested ecosystem: a case study from Montserrat - Kelvin S.-H. Peh; Andrew Balmford; Jennifer C. Birch; Claire Brown; Stuart H. M. Butchart; James Daley; Jeffrey Dawson; Gerard Gray; Francine M. R. Hughes; Stephen Mendes; James Millett; Alison J. Stattersfield; et al. (Biological Invasions, 2015)

Functional traits, land‐use change and the structure of present and future bird communities in tropical forests - Tim Newbold; Jörn P. W. Scharlemann; Stuart H. M. Butchart; Çağan H. Şekercioğlu; Lucas Joppa; Rob Alkemade; Drew W. Purves (Global Ecology and Biogeography, 2014)
Aim Habitat loss continues to cause loss of biodiversity. To quantify the effects of land‐use change on the diversity and composition of ecological communities – in terms of functional groups – we make modelled estimates of the impact of past and future (to 2050) land‐use change on the overall diversity and dietary guild structure of tropical forest bird communities. Location Tropical and subtropical forests (40° S to 40° N ). Methods Using a likelihood‐based model, we project the impact of land‐use intensity on the diversity and functional structure of tropical forest bird communities, including an estimation of uncertainty. To explore the extent to which predicted impacts are determined by the inherent sensitivity of communities because of the traits possessed by the species present, we quantify communities in terms of trait composition and explore relationships between trait composition and diversity/guild loss. Results We estimate that habitat loss has led to an average decrease of 4% in total abundance, but with marked differences across different guilds, leading to substantial changes in community composition: an 11.4% loss of frugivores, 7.8% loss of nectarivores and 7.3% loss of insectivores, and a 4.0% gain of other herbivores. Projected land‐use change is predicted to result in average future losses of 1% of total abundance, 1% of each of frugivores, nectarivores and insectivores, but no average change in the abundance of other herbivores. Past and future changes have varied substantially across the biome, owing to variation in land‐use change and in the initial trait composition of communities. Main conclusions We predict that marked changes in community structure have occurred in the past and will occur in the future, with disproportionate losses of frugivores, nectarivores and insectivores compared with other species; these species are known to provide important ecosystem services. In the past, South America has been particularly strongly affected, while Southeast Asia will experience the strongest impacts in the future.

The Biogeography of Globally Threatened Seabirds and Island Conservation Opportunities - DENA R. SPATZ; KELLY M. NEWTON; REINA HEINZ; BERNIE TERSHY; NICK D. HOLMES; STUART H. M. BUTCHART; DONALD A. CROLL (Conservation Biology, 2014)
Seabirds are the most threatened group of marine animals; 29% of species are at some risk of extinction. Significant threats to seabirds occur on islands where they breed, but in many cases, effective island conservation can mitigate these threats. To guide island‐based seabird conservation actions, we identified all islands with extant or extirpated populations of the 98 globally threatened seabird species, as recognized on the International Union for Conservation of Nature Red List, and quantified the presence of threatening invasive species, protected areas, and human populations. We matched these results with island attributes to highlight feasible island conservation opportunities. We identified 1362 threatened breeding seabird populations on 968 islands. On 803 (83%) of these islands, we identified threatening invasive species (20%), incomplete protected area coverage (23%), or both (40%). Most islands with threatened seabirds are amenable to island‐wide conservation action because they are small (57% were 2 ), uninhabited (74%), and occur in high‐ or middle‐income countries (96%). Collectively these attributes make islands with threatened seabirds a rare opportunity for effective conservation at scale. La Biogeografía de Aves Marinas Amenazadas Globalmente y las Oportunidades de Conservación en Islas

Mechanisms underpinning climatic impacts on natural populations: altered species interactions are more important than direct effects - Nancy Ockendon; David J. Baker; Jamie A. Carr; Elizabeth C. White; Rosamunde E. A. Almond; Tatsuya Amano; Esther Bertram; Richard B. Bradbury; Cassie Bradley; Stuart H. M. Butchart; Nathalie Doswald; Wendy Foden; et al. (Global Change Biology, 2014)
Shifts in species' distribution and abundance in response to climate change have been well documented, but the underpinning processes are still poorly understood. We present the results of a systematic literature review and meta‐analysis investigating the frequency and importance of different mechanisms by which climate has impacted natural populations. Most studies were from temperate latitudes of North America and Europe; almost half investigated bird populations. We found significantly greater support for indirect, biotic mechanisms than direct, abiotic mechanisms as mediators of the impact of climate on populations. In addition, biotic effects tended to have greater support than abiotic factors in studies of species from higher trophic levels. For primary consumers, the impact of climate was equally mediated by biotic and abiotic mechanisms, whereas for higher level consumers the mechanisms were most frequently biotic, such as predation or food availability. Biotic mechanisms were more frequently supported in studies that reported a directional trend in climate than in studies with no such climatic change, although sample sizes for this comparison were small. We call for more mechanistic studies of climate change impacts on populations, particularly in tropical systems.

Evaluating the effectiveness of conservation site networks under climate change: accounting for uncertainty - Robert Bagchi; Mike Crosby; Brian Huntley; David G. Hole; Stuart H. M. Butchart; Yvonne Collingham; Mohit Kalra; Jagadish Rajkumar; Asad Rahmani; Mitra Pandey; Hum Gurung; Le Trong Trai; et al. (Global Change Biology, 2013)
We forecasted potential impacts of climate change on the ability of a network of key sites for bird conservation (Important Bird Areas; IBA s) to provide suitable climate for 370 bird species of current conservation concern in two Asian biodiversity hotspots: the Eastern Himalaya and Lower Mekong. Comparable studies have largely not accounted for uncertainty, which may lead to inappropriate conclusions. We quantified the contribution of four sources of variation (choice of general circulation models, emission scenarios and species distribution modelling methods and variation in species distribution data) to uncertainty in forecasts and tested if our projections were robust to these uncertainties. Declines in the availability of suitable climate within the IBA network by 2100 were forecast as ‘extremely likely’ for 45% of species, whereas increases were projected for only 2%. Thus, we predict almost 24 times as many ‘losers’ as ‘winners’. However, for no species was suitable climate ‘extremely likely’ to be completely lost from the network. Considerable turnover (median = 43%, 95% CI = 35–69%) in species compositions of most IBA s were projected by 2100. Climatic conditions in 47% of IBA s were projected as ‘extremely likely’ to become suitable for fewer priority species. However, no IBA was forecast to become suitable for more species. Variation among General Circulation Models and Species Distribution Models contributed most to uncertainty among forecasts. This uncertainty precluded firm conclusions for 53% of species and IBA s because 95% confidence intervals included projections of no change. Considering this uncertainty, however, allows robust recommendations concerning the remaining species and IBA s. Overall, while the IBA network will continue to sustain bird conservation, climate change will modify which species each site will be suitable for. Thus, adaptive management of the network, including modified site conservation strategies and facilitating species' movement among sites, is critical to ensure effective future conservation.

Toward a Management Framework for Networks of Protected Areas in the Face of Climate Change - DAVID G. HOLE; BRIAN HUNTLEY; JULIUS ARINAITWE; STUART H. M. BUTCHART; YVONNE C. COLLINGHAM; LINCOLN D. C. FISHPOOL; DEBORAH J. PAIN; STEPHEN G. WILLIS (Conservation Biology, 2011)
Networks of sites of high importance for conservation of biological diversity are a cornerstone of current conservation strategies but are fixed in space and time. As climate change progresses, substantial shifts in species’ ranges may transform the ecological community that can be supported at a given site. Thus, some species in an existing network may not be protected in the future or may be protected only if they can move to sites that in future provide suitable conditions. We developed an approach to determine appropriate climate‐change adaptation strategies for individual sites within a network that was based on projections of future changes in the relative proportions of emigrants (species for which a site becomes climatically unsuitable), colonists (species for which a site becomes climatically suitable), and persistent species (species able to remain within a site despite the climatic change). Our approach also identifies key regions where additions to a network could enhance its future effectiveness. Using the sub‐Saharan African Important Bird Area (IBA) network as a case study, we found that appropriate conservation strategies for individual sites varied widely across sub‐Saharan Africa, and key regions where new sites could help increase network robustness varied in space and time. Although these results highlight the potential difficulties within any planning framework that seeks to address climate‐change adaptation needs, they demonstrate that such planning frameworks are necessary, if current conservation strategies are to be adapted effectively, and feasible, if applied judiciously.

Projected impacts of climate change on a continent‐wide protected area network - David G. Hole; Stephen G. Willis; Deborah J. Pain; Lincoln D. Fishpool; Stuart H. M. Butchart; Yvonne C. Collingham; Carsten Rahbek; Brian Huntley (Ecology Letters, 2009)
Despite widespread concern, the continuing effectiveness of networks of protected areas under projected 21st century climate change is uncertain. Shifts in species’ distributions could mean these resources will cease to afford protection to those species for which they were originally established. Using modelled projected shifts in the distributions of sub‐Saharan Africa’s entire breeding avifauna, we show that species turnover across the continent’s Important Bird Area (IBA) network is likely to vary regionally and will be substantial at many sites (> 50% at 42% of IBAs by 2085 for priority species). Persistence of suitable climate space across the network as a whole, however, is notably high, with 88–92% of priority species retaining suitable climate space in ≥ 1 IBA(s) in which they are currently found. Only 7–8 priority species lose climatic representation from the network. Hence, despite the likelihood of significant community disruption, we demonstrate that rigorously defined networks of protected areas can play a key role in mitigating the worst impacts of climate change on biodiversity.

A Standard Lexicon for Biodiversity Conservation: Unified Classifications of Threats and Actions - NICK SALAFSKY; DANIEL SALZER; ALISON J. STATTERSFIELD; CRAIG HILTON‐TAYLOR; RACHEL NEUGARTEN; STUART H. M. BUTCHART; BEN COLLEN; NEIL COX; LAWRENCE L. MASTER; SHEILA O'CONNOR; DAVID WILKIE (Conservation Biology, 2008)
An essential foundation of any science is a standard lexicon. Any given conservation project can be described in terms of the biodiversity targets, direct threats, contributing factors at the project site, and the conservation actions that the project team is employing to change the situation. These common elements can be linked in a causal chain, which represents a theory of change about how the conservation actions are intended to bring about desired project outcomes. If project teams want to describe and share their work and learn from one another, they need a standard and precise lexicon to specifically describe each node along this chain. To date, there have been several independent efforts to develop standard classifications for the direct threats that affect biodiversity and the conservation actions required to counteract these threats. Recognizing that it is far more effective to have only one accepted global scheme, we merged these separate efforts into unified classifications of threats and actions, which we present here. Each classification is a hierarchical listing of terms and associated definitions. The classifications are comprehensive and exclusive at the upper levels of the hierarchy, expandable at the lower levels, and simple, consistent, and scalable at all levels. We tested these classifications by applying them post hoc to 1191 threatened bird species and 737 conservation projects. Almost all threats and actions could be assigned to the new classification systems, save for some cases lacking detailed information. Furthermore, the new classification systems provided an improved way of analyzing and comparing information across projects when compared with earlier systems. We believe that widespread adoption of these classifications will help practitioners more systematically identify threats and appropriate actions, managers to more efficiently set priorities and allocate resources, and most important, facilitate cross‐project learning and the development of a systematic science of conservation.

Use and misuse of the IUCN Red List Criteria in projecting climate change impacts on biodiversity - H. RESIT AKÇAKAYA; STUART H. M. BUTCHART; GEORGINA M. MACE; SIMON N. STUART; CRAIG HILTON‐TAYLOR (Global Change Biology, 2006)
Recent attempts at projecting climate change impacts on biodiversity have used the IUCN Red List Criteria to obtain estimates of extinction rates based on projected range shifts. In these studies, the Criteria are often misapplied, potentially introducing substantial bias and uncertainty. These misapplications include arbitrary changes to temporal and spatial scales; confusion of the spatial variables; and assume a linear relationship between abundance and range area. Using the IUCN Red List Criteria to identify which species are threatened by climate change presents special problems and uncertainties, especially for shorter‐lived species. Responses of most species to future climate change are not understood well enough to estimate extinction risks based solely on climate change scenarios and projections of shifts and/or reductions in range areas. One way to further such understanding would be to analyze the interactions among habitat shifts, landscape structure and demography for a number of species, using a combination of models. Evaluating the patterns in the results might allow the development of guidelines for assigning species to threat categories, based on a combination of life history parameters, characteristics of the landscapes in which they live, and projected range changes.

Biodiversity Indicators Based on Trends in Conservation Status: Strengths of the IUCN Red List Index - STUART H. M. BUTCHART; H. RESIT AKCAKAYA; ELIZABETH KENNEDY; CRAIG HILTON‐TAYLOR (Conservation Biology, 2006)